STRATEGI INOVASI E-COMMERCE DALAM MENGHADAPI GLOBALISASI ( STUDI KASUS JD.ID) - Setyo Budi; Dewi Agustini Santoso; Suharnawi Suharnawi (Program Studi Sistem Informasi, Universitas Banten Jaya, 2023)
Advances in information technology are one of the fundamental things in technological development that cannot be stopped, this will continue to grow to be large and can provide a large level of change in the pattern of people's lives. E-commerce can be said as the development of information technology. And one company that does this is JD.ID. JD. ID is an e-commerce company that has the positioning of